Method for preventing and treating pests - ZHU WEIPING; ZHANG JIAXIN; ZHENG JIAXIN; FANG HONGLONG; XU YUFANG; YANG YANGYANG; QIAN XUHONG (2024)
The invention relates to the field of biotechnology and pesticide science. The invention provides an application of separated polynucleotide as a target in preparation of an inhibiting or silencing target of an interference molecule for specifically interfering with pest gene expression or inhibiting pest growth, and the pest gene is selected from chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene, chitin synthetase gene or chitin synthetase gene. The polynucleotide is selected from the following sequences: (1) a sequence as shown in SEQ ID NO: 13 or 14 or a complementary sequence thereof; (2) any polynucleotide sequence hybridized with the sequence limited in (1) under strict conditions; and (3) any polynucleotide sequence having at least 70% or more sequence consistency with the sequence defined in (1). 本发明涉及生物技术和农药学领域。本发明提供分离的多核苷酸作为靶标在制备特异性干扰有害生